La inmunización de lechones precebos con linfocitos alogénicos de cerdos adultos, no afecto la incidencia de rinitis atrófica ni la productividad durante la ceba, en una granja con problemas respiratorios (1999)
ABSTRACT: This study was designed to evaluate if lymphocyte immunotherapy could improve the performance of growing piglets from a farm with a high incidence of respiratory diseases. Healthy finishing pigs from the same farm were bled by jugular puntion and peripheral blood mononuclear cells were obtained by gradient (Histopaque D 0 1077). Three groups of weaned piglets were selected at 7 day after weaning and random assigned to inoculation with pooled allogeneic lymphocytes (7.5 x 107 cell/doses) in 1 ml saline solution (alloimmunized group, n = 80) or 1 ml saline (Control group, n = 80). Morbidity and mortality rates and growth-fattening performance were evaluated from inoculation to slaughter by daily clinical physical evaluation or average daily gain and total weight gain, respectively. No statistical significant differences between groups were found for any of the productive traits evaluated (p > 0.05); however middle rhinitis tended to increase (p = 0.07) in alloinmmunized than control groups, although the difference was not statistically significant when overall rhinitis was evaluated (p > 0.05). These results suggest that allogeneic lymphocyte immunotherapy did not have effect on the incidence of respiratory diseases in a farm with high frequency of respiratory problems and support similar data found with lymphocytes isolated from lymph nodes which did not have an effect on productive traits.